Reliability and validity of the Korean version of the Caregiver Burden Inventory. Issue 3 (September 2021) - Uhm, Kyeong Eun; Jung, Heeyoune; Oh-Park, Mooyeon; Lee, Bo Ram; Kim, Eun Joo; Kim, Jung Hwan; Lee, Seung Ah; Shin, Jinyoung; Kim, Yoon-Sook; Hyun, Cheolhwan; Ko, Nayeon; Lee, Jongmin
Abstract : The purpose of this study was to demonstrate the reliability and validity of the Korean version of the Caregiver Burden Inventory (CBI). The study was conducted as a multicenter cross-sectional survey for caregivers caring for patients with disabilities in outpatient or inpatient rehabilitation clinics. Sociodemographic characteristics and health-related quality of life were collected via questionnaires. The CBI and Burden Interview (BI) were administered, after which internal consistency and factor analysis of the CBI and correlation between the CBI and BI were explored. A total of 151 caregivers participated. The mean age of caregivers was 53.7 ± 12.4 years, and 80.8 % were women. The majority of caregivers were the main caregivers of stroke, spinal cord injury or traumatic brain injury. The factor analysis confirmed its five factorial structure. The time-dependence and physical burden scores of CBI were higher than those of other factors. All five-dimensional and total scores of CBI showed high internal consistency and were well correlated with BI. In conclusion, the CBI has proven its reliability, construct validity and concurrent validity for caregivers of disabled people and has shown its advantage as a multidimensional measure.